Analysis of male and female Olympic swimmers in the 100-meter events - Kennedy, P.; Brown, P.; Chengalur, S. N.; Nelson, R. C. (Journal of Applied Biomechanics, 1990)
Stroke rate, length, final time, age, and height were assessed across the four 100 m events' heats at the Olympic Games. It was found that: 1.the higher the stroke rate, the shorter the stroke length; 2.successful swimmers had longer stroke lengths; 3.stroke rate was not related to body size but stroke length was; 4.taller swimmers had longer stroke lengths; 5.age was only important in the women's events being negatively correlated with final time in three of the four events (breaststroke not being related); and 6.males across the four events were 10.6% faster, 11.5% older, 7.3% taller, and had 9.7% longer stroke lengths but had only 1% greater stroke rate. Implication: Stroke length and rate were used in various combinations by many swimmers to achieve good performance times. It would seem that stroke length should be a priority for instructional emphasis.